A composite hollow fiber nanofiltration membrane and its preparation method and application

By introducing amino-functionalized NH2-ZIF-8 material and polycationic electrolyte into the nanofiltration membrane, and using layer-by-layer self-assembly method, the problem of insufficient water flux and retention rate of the existing nanofiltration membrane was solved, and an efficient composite hollow fiber nanofiltration membrane was prepared.

CN119175010BActive Publication Date: 2025-04-22北京诺滤新材料科技有限公司 +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411542561.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-04-22
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

Existing positive charge composite nanofiltration membranes perform poorly in water flux and divalent salt retention, and the preparation process is complex and safe.

Method used

The amino-functionalized NH2-ZIF-8 material was synthesized in situ by coordination and mixed with polycationic electrolyte. The composite hollow fiber nanofiltration membrane was prepared by layer-by-layer self-assembly method to alternate coatings on the hollow fiber ultrafiltration membrane.

Benefits of technology

It realizes a nanofiltration membrane with high throughput and high divalent salt retention rate, and the preparation method is simple and easy to implement, with high safety, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119175010B_ABST
    Figure CN119175010B_ABST
Patent Text Reader

Abstract

The present invention provides a composite hollow fiber nanofiltration membrane and a preparation method and application thereof, belonging to the technical field of nanofiltration membranes. The present invention adopts 2-aminoimidazole to replace 2-methylimidazole in the metal organic framework ZIF-8 structure in situ to prepare amino-functionalized NH2-ZIF-8; then NH2-ZIF-8 is mixed with a polycation electrolyte to obtain a polycation electrolyte containing NH2-ZIF-8, and then the polycation electrolyte containing NH2-ZIF-8 and a polyanion electrolyte are used to perform alternating coating treatment on a hollow fiber ultrafiltration membrane to prepare a composite hollow fiber nanofiltration membrane. Among them, NH2-ZIF-8 containing an amino structure can increase the positive charge density of the nanofiltration membrane, make the hydrophilicity of the nanofiltration membrane better, not only can the retention rate of divalent cations be improved, but also has a higher pure water flux.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nanofiltration membranes, and in particular to a composite hollow fiber nanofiltration membrane and a preparation method and application thereof. Background Art

[0002] Nanofiltration membranes play a key role in water treatment, separation technology and environmental protection, especially in removing tiny pollutants, heavy metal ions and organic matter. These membrane technologies can effectively intercept particles with a diameter between 1 and 10 nm, help remove fine suspended matter, viruses and bacteria in water, while allowing water molecules and some beneficial minerals to pass through. The efficient separation ability of nanofiltration membranes can not only significantly improve water quality and reduce the concentration of harmful substances, but also retain elements that are beneficial to human health, so it is particularly important in drinking water purification.

[0003] At present, great progress has been made in the field of nanofiltration membranes with high permeability separation performance. Existing commercial nanofiltration membrane materials are based on traditional interfacial polymerization technology. Their permeability separation performance is determined by the polyamide separation cortex, and the separation mechanism is mainly based on pore size screening and Donnan exclusion effect. However, the surface of polyamide membrane materials is negatively charged, and the Donnan effect has little effect on the separation performance of monovalent / divalent cations. In order to solve this problem, researchers have focused on positively charged nanofiltration membranes because they have strong hydrophilicity and effective repulsion to positively charged ions. This excellent hydrophilicity enables positively charged nanofiltration membranes to achieve higher water flux.

[0004] Patent CN105013333A discloses a positively charged composite nanofiltration membrane and a preparation method thereof. The membrane firstly composites a base membrane on a polypropylene or polyacrylonitrile nonwoven fabric, and then adds a positively charged separation layer to form a composite nanofiltration membrane. Under an operating pressure of 8 bar, the water flux of the membrane is 16 to 20 L / (m·h), the water flux is relatively low, and the preparation process is relatively complicated. Patent CN109794166A discloses a positively charged composite nanofiltration membrane and a preparation method thereof. The composite nanofiltration membrane uses a modified meta-aramid hollow fiber membrane as a base membrane, and uses positively charged polyelectrolytes, polyamines and polyacyl chlorides on the surface of the base membrane to form an ultra-thin polyamide layer through interfacial polymerization. The retention rate of magnesium sulfate is only between 90% and 95%, but the preparation process temperature is -25°C to modify the aramid polymer, and the polymer is dried at 120°C, and the preparation process uses concentrated sulfuric acid, which has a low safety factor.

[0005] Therefore, the existing positively charged composite nanofiltration membranes either have complicated preparation methods or have problems with low flux and salt retention rate. Summary of the invention

[0006] The object of the present invention is to provide a composite hollow fiber nanofiltration membrane and a preparation method and application thereof, which has high divalent salt retention rate and high flux, and the preparation method is simple and easy.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] The present invention provides a method for preparing a composite hollow fiber nanofiltration membrane, comprising the following steps:

[0009] Mixing 2-methylimidazole, 2-aminoimidazole and a first organic solvent to obtain an imidazole solution;

[0010] dispersing the zinc salt in a second organic solvent to obtain a zinc salt dispersion;

[0011] The imidazole solution is mixed with the zinc salt dispersion to carry out coordination reaction to obtain NH2-ZIF-8 material;

[0012] The NH2-ZIF-8 material is mixed with a polycation electrolyte to obtain an amino-structured polycation electrolyte;

[0013] The composite hollow fiber nanofiltration membrane is obtained by using a layer-by-layer self-assembly method and using polyelectrolyte solutions with opposite charges to perform alternate coating treatment on the hollow fiber ultrafiltration membrane.

[0014] The polyelectrolyte in the polyelectrolyte solution with opposite charges is the polycation electrolyte or polyanion electrolyte containing an amino structure.

[0015] Preferably, the molar amount of the 2-aminoimidazole is 10 to 100% of the total molar amount of the 2-methylimidazole and the 2-aminoimidazole.

[0016] Preferably, the molar ratio of zinc ions to the total molar amount of 2-methylimidazole and 2-aminoimidazole in the zinc salt is 1:1 to 1:60.

[0017] Preferably, the coordination reaction time is 30 to 60 minutes.

[0018] Preferably, the molar amount of the NH2-ZIF-8 material is 1 to 70% of the molar amount of the amino-containing polycationic electrolyte; the mixing time of the NH2-ZIF-8 material and the polycationic electrolyte is 30 to 60 minutes, and the temperature is 15 to 25°C.

[0019] Preferably, the polycation electrolyte comprises one of polydimethyldiallylammonium chloride, polyethyleneimine, polyethyleneamine and polyacrylamide;

[0020] The polyanion electrolyte includes one of polyacrylic acid, polyaminoacetic acid, polystyrene sulfonic acid and polysulfuric acid.

[0021] Preferably, the total number of polyelectrolyte coating layers formed by the alternating coating process is 1 to 20 layers;

[0022] The temperature of the alternating coating treatment is independently 15-25°C.

[0023] Preferably, when the polyelectrolyte coating is a polycationic coating, the pH of the polyelectrolyte solution used is 3.5 to 4.5; when the polyelectrolyte coating is a polyanionic coating, the pH of the polyelectrolyte solution used is 6.0 to 8.0.

[0024] The present invention provides a composite hollow fiber nanofiltration membrane prepared by the preparation method described in the above technical solution.

[0025] The present invention provides the application of the composite hollow fiber nanofiltration membrane described in the above technical solution in the fields of surface water treatment, biopharmaceuticals, seawater desalination or soil and groundwater remediation.

[0026] The invention provides a preparation method of a composite hollow fiber nanofiltration membrane. The invention adopts 2-aminoimidazole to perform in-situ substitution on 2-methylimidazole in a metal organic framework ZIF-8 structure to prepare an amino functionalized NH2-ZIF-8 metal organic framework material; then the NH2-ZIF-8 containing amino groups is mixed with a polycation electrolyte to obtain a polycation electrolyte containing NH2-ZIF-8, and then the polycation electrolyte containing NH2-ZIF-8 and a polyanion electrolyte are alternately coated on a hollow fiber ultrafiltration membrane by a layer-by-layer self-assembly method to prepare a composite hollow fiber nanofiltration membrane. The in-situ substitution method of the invention can introduce amino groups without destroying the ZIF-8 structure, thereby enhancing the hydrophilicity of the metal organic framework and thus enhancing the hydrophilicity of the nanofiltration membrane, and at the same time, the amino structure of NH2-ZIF-8 can increase the positive charge density of the polycation electrolyte and the nanofiltration membrane, so that the nanofiltration membrane of the invention can increase the interception rate of divalent cations. Moreover, the present invention adopts a layer-by-layer self-assembly method to prepare the nanofiltration membrane, and an amino-containing polycation electrolyte and a polyanion electrolyte with opposite charges are assembled under the action of entropy increase to obtain a high-flux composite hollow fiber nanofiltration membrane. Therefore, the hollow fiber nanofiltration membrane of the present invention has a higher pure water flux.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] The NH2-ZIF-8 material containing amino functionalization was synthesized in situ by coordination, and a high-throughput hollow fiber nanofiltration membrane was prepared by layer-by-layer self-assembly method. It has good hydrophilic properties and the water contact angle is reduced to 35°, which is a hydrophilic membrane. The water flux of the nanofiltration membrane is 45Lm -2 h -1 above.

[0029] The metal organic framework material added to the polycation electrolyte used in the present invention contains positively charged amino groups, which can increase the positive charge density of the nanofiltration membrane, so that the interception rate of the nanofiltration membrane for magnesium sulfate is as high as more than 96%.

[0030] The layer-by-layer self-assembly method adopted by the present invention is based on water solvent, and the preparation process is green and environmentally friendly, and the cost is low, and it is easier to industrialize production.

[0031] The hollow fiber nanofiltration membrane prepared by the present invention can also be adjusted according to specific application requirements when treating various water qualities (such as industrial wastewater, urban sewage, seawater desalination, etc.) to meet the use requirements under different industrial and environmental conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The structure diagrams of the polyanion-cation electrolyte (a) and NH2-ZIF-8 (b) in the present invention;

[0033] Figure 2 The synthesis process of ZIF-8 and NH2-ZIF-8 (25) nanoparticles in Example 1 of the present invention;

[0034] Figure 3 XRD diagram of ZIF-8 and NH2-ZIF-8(25) nanoparticles in Example 1 of the present invention;

[0035] Figure 4 FTIR images of ZIF-8 and NH2-ZIF-8(25) nanoparticles in Example 1 of the present invention;

[0036] Figure 5 The liquid NMR images of ZIF-8 and NH2-ZIF-8 (25) nanoparticles in Example 1 of the present invention;

[0037] Figure 6 The SEM images of NH2-ZIF-8 nanoparticles at different 2-aminoimidazole molar percentages in Comparative Example 1 and Examples 1 to 3 of the present invention;

[0038] Figure 7 The nanofiltration membrane contact angle diagrams at different 2-aminoimidazole mole percentages in Comparative Example 1 and Examples 1 to 3 of the present invention;

[0039] Figure 8 The nanofiltration membrane water flux diagram at different 2-aminoimidazole mole percentages in Comparative Example 1 and Examples 1 to 3 of the present invention;

[0040] Fig. 9 The salt rejection diagram of the nanofiltration membrane at different 2-aminoimidazole molar percentages in Comparative Example 1 and Examples 1 to 3 of the present invention. DETAILED DESCRIPTION

[0041] In the present invention, unless otherwise specified, the required preparation materials or reagents are commercially available products well known to those skilled in the art.

[0042] The present invention provides a method for preparing a composite hollow fiber nanofiltration membrane, comprising the following steps:

[0043] Mixing 2-methylimidazole, 2-aminoimidazole and a first organic solvent to obtain an imidazole solution;

[0044] dispersing the zinc salt in a second organic solvent to obtain a zinc salt dispersion;

[0045] The imidazole solution is mixed with the zinc salt dispersion to carry out coordination reaction to obtain NH2-ZIF-8 material;

[0046] The NH2-ZIF-8 material is mixed with a polycation electrolyte to obtain an amino-structured polycation electrolyte;

[0047] The composite hollow fiber nanofiltration membrane is obtained by using a layer-by-layer self-assembly method and using polyelectrolyte solutions with opposite charges to perform alternate coating treatment on the hollow fiber ultrafiltration membrane.

[0048] The polyelectrolyte in the polyelectrolyte solution with opposite charges is the polycation electrolyte or polyanion electrolyte containing an amino structure.

[0049] In the present invention, the molar amount of the 2-aminoimidazole is 10 to 100% of the total molar amount of the 2-methylimidazole and the 2-aminoimidazole, more preferably 25 to 75%, and further preferably 50 to 70%.

[0050] The present invention has no special limitation on the concentrations of 2-methylimidazole and 2-aminoimidazole in the imidazole solution, and the concentrations can be adjusted according to actual needs to ensure that the coordination reaction proceeds in order.

[0051] In the present invention, the concentration of the zinc salt dispersion is preferably 0.01 to 1 mol / L, more preferably 0.1 to 0.5 mol / L; the molar ratio of zinc ions to the total molar amount of 2-methylimidazole and 2-aminoimidazole in the zinc salt is preferably 1:1 to 1:60, more preferably 1:20.

[0052] In the present invention, the first organic solvent and the second organic solvent are independently preferably methanol; the zinc salt is preferably zinc nitrate hexahydrate.

[0053] The present invention preferably dissolves 2-methylimidazole and 2-aminoimidazole in a first solvent to obtain an imidazole solution; disperses the zinc salt in a second solvent, and performs ultrasonic treatment until the zinc salt is completely dissolved to obtain a zinc salt dispersion; adds the imidazole solution to the zinc salt dispersion and stirs, performs a coordination reaction under ultrasonic conditions, washes the obtained product to remove unreacted raw materials, performs centrifugal separation, and dries the obtained precipitate to obtain a metal organic framework material (NH2-ZIF-8) containing an amino structure.

[0054] In the present invention, the coordination reaction time is preferably 30 to 60 minutes, more preferably 40 to 50 minutes.

[0055] The cleaning reagent used in the present invention is preferably methanol, and the number of cleaning times is preferably 3 to 6 times, more preferably 4 times; the speed of the centrifugal separation is preferably 1200 to 1500 r / min; the temperature of the drying is preferably 60 to 100°C, more preferably 80°C, and the time is preferably 8 to 12h, more preferably 10h.

[0056] In the present invention, the NH2-ZIF-8 contains an imidazole structure and is functionalized with an amino group at the end, and each polymerization unit thereof contains an imidazole structure and an amino group. Figure 1 Middle (b).

[0057] The present invention mixes the NH2-ZIF-8 material with a polycation electrolyte to obtain an amino structure-containing polycation electrolyte.

[0058] like Figure 1 As shown in (a), in the present invention, the polycationic electrolyte preferably includes one of polydimethyldiallylammonium chloride (PDADMAC), polyethyleneimine (PEI), polyethyleneamine (PVAm) and polyacrylamide (PAM).

[0059] In the present invention, the molar amount of the NH2-ZIF-8 material is 1-70% of the molar amount of the amino structure-containing polycationic electrolyte, more preferably 10-60%, and further preferably 30-50%; the mixing time of the NH2-ZIF-8 material and the polycationic electrolyte is preferably 30-60 minutes, more preferably 40 minutes, and the temperature is preferably 15-25° C., more preferably 20° C. During the mixing process, the specific amino structure of NH2-ZIF-8 interacts with the cationic part of the polycationic electrolyte to form a stable composite material.

[0060] The invention adopts a layer-by-layer self-assembly method, and uses polyelectrolyte solutions with opposite charges to perform alternating coating treatment on a hollow fiber ultrafiltration membrane to obtain a composite hollow fiber nanofiltration membrane.

[0061] The present invention has no particular limitation on the type or specification of the hollow fiber ultrafiltration membrane, and any corresponding commercially available product known in the art may be used; in the embodiment of the present invention, it is specifically a polyethersulfone hollow fiber ultrafiltration membrane.

[0062] In the present invention, the polyelectrolyte in the polyelectrolyte solution with opposite charges is the polycation electrolyte or polyanion electrolyte containing an amino structure.

[0063] In the present invention, the polyanion electrolyte preferably comprises one of polyacrylic acid (PAA), polyaminoacetic acid (PAAc), polystyrene sulfonic acid (PSS) and polysulfuric acid (PSA), and the structure is as follows: Figure 1 As shown in (a).

[0064] In the present invention, the solvent used for the oppositely charged polyelectrolyte solution is preferably a sodium chloride aqueous solution; the present invention has no special limitation on the concentration of the sodium chloride aqueous solution, which can be adjusted according to actual needs.

[0065] The present invention has no special limitation on the concentration of the polyelectrolyte in the polyelectrolyte solution, which can be adjusted according to actual needs. In an embodiment of the present invention, the concentration of the polyanion electrolyte solution is preferably 4 g / L; the concentration of the polycation electrolyte solution is preferably 10 g / L.

[0066] In the present invention, the method of alternating coating treatment is preferably a static coating method.

[0067] In an embodiment of the present invention, the method of alternating coating treatment is preferably to inject a polyelectrolyte solution with a first charge into the inner cavity of the hollow fiber ultrafiltration membrane through a peristaltic pump, and let it stand for 5 minutes to form a first coating; flush the inner cavity of the membrane with deionized water until the conductivity of the effluent is close to the conductivity of deionized water, and then blow dry the excess liquid in the inner cavity of the membrane with compressed air; then inject another polyelectrolyte solution with an opposite charge into the inner cavity of the hollow fiber membrane containing the first coating, and let it stand for 5 minutes to form a second coating; flush the inner cavity of the membrane with deionized water until the conductivity of the effluent is close to the conductivity of deionized water, and then blow dry the excess liquid in the inner cavity of the membrane with compressed air; alternately repeat the above steps of forming the first coating and the second coating until the desired number of polyelectrolyte coatings are formed.

[0068] In the present invention, the temperature of the alternating coating treatment (ie the temperature of the polyelectrolyte solution) is independently preferably 15 to 25°C, more preferably 20 to 22°C.

[0069] In the present invention, the total number of polyelectrolyte coatings formed by the alternating coating treatment is preferably 1 to 20 layers, more preferably 5 to 15 layers, and further preferably 6 to 8 layers; when the polyelectrolyte in the polyelectrolyte solution with opposite charges is the polycationic electrolyte containing an amino structure, a polycationic coating is formed; when the polyelectrolyte in the polyelectrolyte solution with opposite charges is a polyanionic electrolyte, a polyanionic coating is formed.

[0070] In the present invention, when the polyelectrolyte coating is a polycationic coating, the pH of the polyelectrolyte solution used is 3.5-4.5, and a 1 mol / L hydrochloric acid aqueous solution is used to adjust the pH to the desired pH value; when the polyelectrolyte coating is a polyanionic coating, the pH of the polyelectrolyte solution used is 6.0-8.0, more preferably 7.3, and a 1 mol / L sodium hydroxide aqueous solution is used to adjust the pH to the desired pH value.

[0071] The present invention provides a composite hollow fiber nanofiltration membrane prepared by the preparation method described in the above technical solution. The composite hollow fiber nanofiltration membrane prepared by the present invention is a hollow fiber composite nanofiltration membrane with a metal organic skeleton structure containing an amino structure.

[0072] The present invention provides the application of the composite hollow fiber nanofiltration membrane described in the above technical solution in the fields of surface water treatment, biopharmaceuticals, seawater desalination or soil and groundwater remediation. The present invention has no special limitation on the application method, and the application can be carried out according to methods well known in the art.

[0073] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0074] Example 1

[0075] The preparation method of the composite hollow fiber nanofiltration membrane in this embodiment comprises the following steps:

[0076] like Figure 2 As shown, 1.5 mol 2-methylimidazole and 0.5 mol 2-aminoimidazole (i.e., the molar percentage of 2-aminoimidazole is 25%) were dissolved in 200 mL methanol, 0.1 mol Zn(NO3)2·6H2O was dispersed in 200 mL methanol, the two liquids were mixed by ultrasound for 40 min, washed with methanol 4 times, and then centrifuged at 1500 r / min to obtain a precipitate, which was dried at 80 °C for 10 h to obtain NH2-ZIF-8 (25);

[0077] 0.3 mol NH2-ZIF-8(25) and 0.7 mol polydimethyldiallyl ammonium chloride (PDADMAC) powder were mixed to obtain a polycationic electrolyte PDADMAC containing NH2-ZIF-8(25), wherein the molar percentage of NH2-ZIF-8(25) was 30%;

[0078] The polyethersulfone hollow fiber ultrafiltration membrane was coated with polyelectrolyte solutions with opposite charges alternately by layer-by-layer self-assembly method, wherein the polycationic electrolyte was the polycationic electrolyte PDADMAC containing NH2-ZIF-8(25), and the polyanionic electrolyte was polystyrene sulfonic acid (PSS):

[0079] (1) A 4 g / L PSS solution (solute is PSS, solvent is 0.5 M NaCl aqueous solution obtained by dissolving 0.5 mol sodium chloride in 1 L deionized water, and pH=7.3 is adjusted using 1 M sodium hydroxide aqueous solution) and the temperature of the polyelectrolyte solution is 20°C, and injected into the lumen of the polyethersulfone hollow fiber ultrafiltration membrane through a peristaltic pump, and allowed to stand for 5 min to form the first layer of coating; the lumen of the membrane is flushed with deionized water for 4 min until the conductivity of the eluate is close to that of deionized water, and then the excess liquid in the lumen of the membrane is blown dry with compressed air;

[0080] (2) injecting 10 g / L polycationic electrolyte PDADMAC solution containing NH2-ZIF-8(25) (solute is polycationic electrolyte PDADMAC containing NH2-ZIF-8(25); solvent is 2.5 M NaCl aqueous solution obtained by dissolving 2.5 mol sodium chloride in 1 L deionized water, and pH=3.5 is adjusted using 1 M hydrochloric acid aqueous solution), the temperature of the polyelectrolyte solution is 20°C, and injected into the inner cavity of the hollow fiber membrane coated with PSS through a peristaltic pump, and allowed to stand for 5 minutes to form a second layer of coating; flushing the inner cavity of the membrane with deionized water for 4 minutes until the conductivity of the eluate is close to the conductivity of deionized water, and then blowing the excess liquid in the membrane cavity with compressed air;

[0081] (3) Repeat the above steps (1) and (2) alternately until 6 polyelectrolyte coating monolayers are formed to obtain a polyelectrolyte composite hollow fiber nanofiltration membrane containing NH2-ZIF-8 (25).

[0082] Comparative Example 1

[0083] like Figure 2As shown, 0.5 mol 2-aminoimidazole and 1.5 mol 2-methylimidazole (i.e., the molar percentage of 2-aminoimidazole is 25%) are dispersed in 200 mL of methanol, 0.1 mol Zn(NO3)2·6H2O is dispersed in 200 mL of methanol, the two liquids are mixed by ultrasound for 30 min, washed with methanol three times, and then centrifuged at 1200 r / min to obtain a precipitate, which is dried at 80°C for 10 h to obtain ZIF-8;

[0084] The nanofiltration membrane was prepared using the non-aminated ZIF-8 prepared above according to the method of Example 1, namely NH2-ZIF-8(0).

[0085] Characterization and testing

[0086] Figure 3 These are the XRD patterns of ZIF-8 in Comparative Example 1 and NH2-ZIF-8(25) nanoparticles in Example 1. The XRD patterns of ZIF-8 nanocrystals and NH2-ZIF-8 nanoparticle structures are consistent with the results of simulated ZIF-8 crystals.

[0087] Figure 4 The FTIR images of ZIF-8 in Comparative Example 1 and NH2-ZIF-8 (25) nanoparticles in Example 1 show that in the original ZIF-8, only 1432.6 cm -1 The C=N bond was observed at 1488.3 cm in NH2-ZIF-8(25). -1 The C=N bond was observed at 1432.6 cm -1 and 1488.3cm -1 C=N bond absorption occurs in both peaks. -1 In addition, when 2-aminoimidazole is substituted, the absorption peak at 470 cm in the inner near infrared -1 A new absorption peak was observed at 470 cm-1 in NH2-ZIF-8(25). -1 The absorption peak of 2-aminoimidazole was shown in Figure 2. This indicates that 2-aminoimidazole coordinates with zinc ions to form Zn-N. The Zn-N bond has a higher infrared absorption rate, which may make the coordination ability of the Zn-N bond stronger and make the framework of ZIF-8 more rigid. These results indicate that 2-aminoimidazole was successfully incorporated into the ZIF-8 framework.

[0088] Figure 5The liquid NMR images of ZIF-8 in Comparative Example 1 and NH2-ZIF-8(25) nanoparticles in Example 1 show that the content of 2-aminoimidazole in the NH2-ZIF-8(25) framework is lower than that in the original synthetic solution. This phenomenon can be considered as the competitive coordination between 2-aminoimidazole, 2-methylimidazole and zinc ions. All the above results indicate that 2-aminoimidazole is substituted into the original ZIF-8 structure rather than incorporated into the cavity of ZIF-8.

[0089] Figure 6 The SEM images of NH2-ZIF-8 nanoparticles at different 2-aminoimidazole molar percentages in Comparative Example 1 and Examples 1 to 3 of the present invention are shown, wherein a is NH2-ZIF-8(0), b is NH2-ZIF-8(25), c is NH2-ZIF-8(50), and d is NH2-ZIF-8(75). The NH2-ZIF-8 powder substituted with 2-aminoimidazole exhibits a distinct dodecahedral sodalite structure and higher crystallinity. Compared with the single-ligand ZIF-8 nanocrystals, the size of NH2-ZIF-8(25) increases, the former ranging from 50-70nm, while the latter ranging from 70-90nm. This indicates that the amino group in 2-aminoimidazole may inhibit the nucleation rate of the crystals while promoting the rapid growth of the crystals.

[0090] Figure 7 The graphs of contact angles of nanofiltration membranes at different molar percentages of 2-aminoimidazole in comparative example 1 and examples 1 to 3 of the present invention are shown, where a is NH2-ZIF-8 (0), b is NH2-ZIF-8 (25), c is NH2-ZIF-8 (50), and d is NH2-ZIF-8 (75); after the polyethersulfone ultrafiltration membrane is coated with polyelectrolyte, the contact angle of the nanofiltration membrane drops from 75° of the ultrafiltration membrane to 35°. The polyelectrolyte coating can significantly reduce the contact angle of the membrane surface, making it easier for water molecules to wet the membrane surface, thereby improving the hydrophilicity.

[0091] Figure 8 The water flux of nanofiltration membranes at different molar percentages of 2-aminoimidazole in Comparative Example 1 and Examples 1 to 3 of the present invention is shown in Figure 3. Under the test condition of 3 bar, the nanofiltration membrane with only unaminated ZIF-8 added has a flux of 36 Lm / L for MgCl2, MgSO4, Na2SO4, and LiCl with a concentration of 500 mg / L. -2 h -1 After adding NH2-ZIF-8(25), amino groups were introduced into the separation layer of the nanofiltration membrane, thereby enhancing the hydrophilicity of the nanofiltration membrane, and the permeability coefficient of the NH2-ZIF-8(25) nanofiltration membrane increased to 46Lm -2 h -1 .

[0092] Fig. 9The salt retention diagram of the nanofiltration membrane at different molar percentages of 2-aminoimidazole in comparative example 1 and examples 1 to 3 of the present invention shows that under the test condition of 3 bar, the nanofiltration membrane with only unaminated ZIF-8 added has the retention capacity of MgSO4>MgCl2>NaCl>Na2SO4 for metal salts with a concentration of 500 mg / L. The retention rates of the membrane for MgCl2 and MgSO4 are 86% and 89% respectively; while the retention rate for Na2SO4 is relatively low, at 20%. After adding NH2-ZIF-8 (25), amino groups are introduced into the separation layer of the nanofiltration membrane, thereby enhancing the positive charge of the nanofiltration membrane and further improving the retention rate for Mg 2+ The retention rates of MgCl2 and MgSO4 were 93% and 96% respectively.

[0093] Example 2

[0094] The preparation method of the composite hollow fiber nanofiltration membrane in this embodiment comprises the following steps:

[0095] 1.0 mol 2-methylimidazole and 1.0 mol 2-aminoimidazole (the molar percentage of 2-aminoimidazole is 50%) were dissolved in 400 mL methanol, 0.1 mol Zn(NO3)2·6H2O was dispersed in 200 mL methanol, ultrasonically treated for 50 min, washed with methanol 4 times, and then centrifuged at 1500 r / min to obtain a precipitate, which was dried at 80°C for 10 h to obtain NH2-ZIF-8(50);

[0096] 0.3 mol NH2-ZIF-8(50) and 0.7 mol polydimethyldiallyl ammonium chloride (PDADMAC) powder were mixed to obtain a polycationic electrolyte PDADMAC containing NH2-ZIF-8(50), wherein the molar percentage of NH2-ZIF-8(50) was 30%;

[0097] The polyethersulfone hollow fiber ultrafiltration membrane was alternately coated with polyelectrolyte solutions with opposite charges by layer-by-layer self-assembly method, wherein the polycationic electrolyte was the polycationic electrolyte PDADMAC containing NH2-ZIF-8(50), and the polyanionic electrolyte was polystyrene sulfonic acid (PSS):

[0098] (1) A 4 g / L PSS solution (solute is PSS, solvent is 0.5 mol sodium chloride dissolved in 1 L deionized water to obtain a 0.5 M NaCl aqueous solution, and a 1 M sodium hydroxide aqueous solution is used to adjust the pH to 7.3) and the temperature of the polyelectrolyte solution is 20 ° C. It is injected into the lumen of the polyethersulfone hollow fiber ultrafiltration membrane through a peristaltic pump and allowed to stand for 5 min to form a first layer of coating; the membrane lumen is flushed with deionized water for 4 min until the conductivity of the eluate is close to that of deionized water, and then the excess liquid in the membrane lumen is blown dry with compressed air;

[0099] (2) injecting 10 g / L polycation electrolyte PDADMAC solution containing NH2-ZIF-8(50) (solute is polycation electrolyte PDADMAC containing NH2-ZIF-8(50), solvent is 2.5 M NaCl aqueous solution obtained by dissolving 2.5 mol sodium chloride in 1 L deionized water, and pH=3.5 is adjusted using 1 M hydrochloric acid aqueous solution), the temperature of the polyelectrolyte solution is 20°C, and injected into the inner cavity of the hollow fiber membrane coated with PSS through a peristaltic pump, and allowed to stand for 5 minutes to form a second layer of coating; flushing the inner cavity of the membrane with deionized water for 4 minutes until the conductivity of the eluate is close to the conductivity of deionized water, and then blowing the excess liquid in the membrane cavity with compressed air;

[0100] (3) Repeating the above steps (1) and (2) alternately until 6 polyelectrolyte coating monolayers are formed, thereby obtaining a polyelectrolyte composite nanofiltration membrane containing NH2-ZIF-8 (50).

[0101] Figure 6 The SEM morphology of NH2-ZIF-8 nanoparticles at different 2-aminoimidazole molar percentages in Comparative Example 1 and Examples 1 to 3 of the present invention, wherein a is NH2-ZIF-8(0), b is NH2-ZIF-8(25), c is NH2-ZIF-8(50), and d is NH2-ZIF-8(75); the powder substituted with 2-aminoimidazole exhibits a distinct dodecahedral sodalite structure and higher crystallinity. The size of NH2-ZIF-8(50) has increased, ranging from 80-110nm. This indicates that the increase in the amino group ratio in 2-aminoimidazole from 25% to 50% promotes the rapid growth of crystals.

[0102] Figure 8 The water flux diagram of the nanofiltration membrane at different molar percentages of 2-aminoimidazole in Comparative Example 1 and Examples 1 to 3 of the present invention is shown in Figure 1. The amino ratio of the added NH2-ZIF-8 is increased from 25% to 50%, and the amino group is introduced into the separation layer of the nanofiltration membrane, thereby enhancing the hydrophilicity of the nanofiltration membrane, and then the permeability coefficient of the NH2-ZIF-8 (50) nanofiltration membrane is increased to 48Lm -2 h -1 .

[0103] Fig. 9 The salt retention diagram of the nanofiltration membrane at different 2-aminoimidazole molar percentages in Comparative Example 1 and Examples 1 to 3 of the present invention is shown in FIG. 1 . The amino group ratio of the added NH2-ZIF-8 is increased from 25% to 50%, and amino groups are introduced into the separation layer of the nanofiltration membrane, thereby enhancing the positive charge of the nanofiltration membrane and thus improving the Mg 2+ The retention rate of magnesium sulfate is as high as 97%.

[0104] Example 3

[0105] The preparation method of the composite hollow fiber nanofiltration membrane in this embodiment comprises the following steps:

[0106] 0.5 mol 2-methylimidazole and 1.5 mol 2-aminoimidazole (the molar percentage of 2-aminoimidazole is 75%) were dissolved in 400 mL methanol, 0.1 mol Zn(NO3)2·6H2O was dispersed in 200 mL methanol, ultrasonically treated for 50 min, washed with methanol 4 times to remove unreacted raw materials, and then centrifuged at 1500 r / min to obtain a precipitate, which was dried at 80°C for 10 h to obtain NH2-ZIF-8(75);

[0107] 0.3 mol NH2-ZIF-8(75) and 0.7 mol polydimethyldiallyl ammonium chloride (PDADMAC) powder were mixed to obtain a polycationic electrolyte PDADMAC containing NH2-ZIF-8(75), wherein the molar percentage of NH2-ZIF-8(75) was 30%;

[0108] The polyethersulfone hollow fiber ultrafiltration membrane is coated with polyelectrolyte solutions with opposite charges alternately by layer-by-layer self-assembly method; wherein the polycation electrolyte is a polycation electrolyte PDADMAC containing NH2-ZIF-8(75), and the polyanion electrolyte is polystyrene sulfonic acid (PSS):

[0109] (1) A 4 g / L PSS solution (solute is PSS, solvent is 0.5 mol sodium chloride dissolved in 1 L deionized water to obtain a 0.5 M NaCl aqueous solution, and a 1 M sodium hydroxide aqueous solution is used to adjust the pH to 7.3) and the temperature of the polyelectrolyte solution is 20°C. The solution is injected into the lumen of the polyethersulfone hollow fiber ultrafiltration membrane through a peristaltic pump and allowed to stand for 5 min to form the first coating layer; the lumen of the membrane is flushed with deionized water for 4 min until the conductivity of the eluate is close to that of deionized water, and then the excess liquid in the lumen of the membrane is blown dry with compressed air;

[0110] (2) injecting 10 g / L polycation electrolyte PDADMAC solution containing NH2-ZIF-8(75) (solute is polycation electrolyte PDADMAC containing NH2-ZIF-8(75), solvent is 2.5 M NaCl aqueous solution obtained by dissolving 2.5 mol sodium chloride in 1 L deionized water, and pH=3.5 is adjusted using 1 M hydrochloric acid aqueous solution), the temperature of the polyelectrolyte solution is 20°C, and injected into the inner cavity of the hollow fiber membrane coated with PSS through a peristaltic pump, and allowed to stand for 5 minutes to form a second layer of coating; flushing the inner cavity of the membrane with deionized water for 4 minutes until the conductivity of the eluate is close to the conductivity of deionized water, and then blowing the excess liquid in the membrane cavity with compressed air;

[0111] (3) The above steps (1) and (2) are repeated alternately until 6 monolayers are formed to obtain a polyelectrolyte composite nanofiltration membrane containing NH2-ZIF-8(75).

[0112] Figure 6 The SEM morphology of NH2-ZIF-8 nanoparticles at different 2-aminoimidazole molar percentages in Comparative Example 1 and Examples 1 to 3 of the present invention, wherein a is NH2-ZIF-8(0), b is NH2-ZIF-8(25), c is NH2-ZIF-8(50), and d is NH2-ZIF-8(75); the powder substituted with 2-aminoimidazole exhibits a distinct dodecahedral sodalite structure and higher crystallinity. The size of NH2-ZIF-8(50) is 90-110nm, while the size of NH2-ZIF-8(75) increases to a range of 100-140nm. This indicates that the increase in the amino group ratio in 2-aminoimidazole from 50% to 75% promotes the rapid growth of crystals.

[0113] Figure 8 The water flux diagram of the nanofiltration membrane under different molar percentages of 2-aminoimidazole in Comparative Example 1 and Examples 1 to 3 of the present invention is shown in Figure 1. The amino ratio of the added NH2-ZIF-8 is increased from 50% to 75%, and the amino group is introduced into the separation layer of the nanofiltration membrane, thereby enhancing the hydrophilicity of the nanofiltration membrane, and then the permeability coefficient of the NH2-ZIF-8 (75) nanofiltration membrane is increased to 51Lm -2 h -1 .

[0114] Fig. 9 The salt retention diagram of the nanofiltration membrane at different 2-aminoimidazole molar percentages in Comparative Example 1 and Examples 1 to 3 of the present invention is shown in FIG. 1 . The amino group ratio of the added NH2-ZIF-8 is increased from 50% to 75%, and amino groups are introduced into the separation layer of the nanofiltration membrane, thereby enhancing the positive charge of the nanofiltration membrane and thus improving the Mg 2+ The retention rate of magnesium sulfate is as high as 98%.

[0115] Example 4

[0116] The preparation method of the composite hollow fiber nanofiltration membrane in this embodiment comprises the following steps:

[0117] NH2-ZIF-8 (50) was prepared according to the method and conditions of Example 2;

[0118] 0.5 mol NH2-ZIF-8(50) and 0.5 mol polyethyleneimine (PEI) powder are mixed to obtain a polycationic electrolyte PEI containing NH2-ZIF-8(50), wherein the molar percentage of NH2-ZIF-8(50) is 50%;

[0119] The polyethersulfone hollow fiber ultrafiltration membrane is coated with polyelectrolyte solutions with opposite charges alternately by layer-by-layer self-assembly method; wherein the polycation electrolyte is a polycation electrolyte PEI containing NH2-ZIF-8(50), and the polyanion electrolyte is polyacrylic acid (PAA):

[0120] (1) A 4 g / L PAA solution (solute is PAA, solvent is 0.5 mol sodium chloride dissolved in 1 L deionized water to obtain a 0.5 M NaCl aqueous solution, and pH is adjusted to 7.3 using a 1 M sodium hydroxide aqueous solution) with a polyelectrolyte solution temperature of 20°C is injected into the lumen of a polyethersulfone hollow fiber ultrafiltration membrane through a peristaltic pump and allowed to stand for 5 min to form a first layer of coating; the lumen of the membrane is flushed with deionized water for 4 min until the conductivity of the eluate is close to that of deionized water, and then the excess liquid in the lumen of the membrane is blown dry with compressed air;

[0121] (2) injecting 10 g / L polycation electrolyte PEI solution containing NH2-ZIF-8(50) (the solute is polycation electrolyte PEI containing NH2-ZIF-8(50), the solvent is 2.5 M NaCl aqueous solution obtained by dissolving 2.5 mol sodium chloride in 1 L deionized water, and the pH is adjusted to 3.5 using 1 M hydrochloric acid aqueous solution), the temperature of the polyelectrolyte solution is 20 ° C, and it is injected into the inner cavity of the hollow fiber membrane coated with PSS through a peristaltic pump, and allowed to stand for 5 minutes to form a second layer of coating; flushing the inner cavity of the membrane with deionized water for 4 minutes until the conductivity of the eluate is close to the conductivity of deionized water, and then blowing the excess liquid in the membrane cavity with compressed air;

[0122] (3) The above steps (1) and (2) are repeated alternately until 6 monolayers are formed to obtain a polyelectrolyte composite nanofiltration membrane containing NH2-ZIF-8 (50).

[0123] When the molar percentage of NH2-ZIF-8(50) in the amino-containing polyelectrolyte was increased from 30% to 50%, the retention rates of the nanofiltration membrane for MgSO4, MgCl2, NaCl and Na2SO4 were 96%, 98%, 63% and 21%, respectively.

[0124] Example 5

[0125] The preparation method of the composite hollow fiber nanofiltration membrane in this embodiment comprises the following steps:

[0126] 0.6 mol 2-methylimidazole and 1.4 mol 2-aminoimidazole (the molar percentage of 2-aminoimidazole is 70%) were dissolved in 400 mL methanol, 0.1 mol Zn(NO3)2·6H2O was dispersed in 200 mL methanol, ultrasonically treated for 50 min, washed with methanol 4 times, and then centrifuged at 1500 r / min to obtain a precipitate, which was dried at 80°C for 10 h to obtain NH2-ZIF-8(70);

[0127] 1.4 mol NH2-ZIF-8(70) and 0.6 mol polyethyleneimine (PEI) were mixed to obtain a polycationic electrolyte PEI containing NH2-ZIF-8(70), wherein the molar percentage of NH2-ZIF-8(70) was 70%;

[0128] The polyethersulfone hollow fiber ultrafiltration membrane was coated with polyelectrolyte solutions with opposite charges alternately by layer-by-layer self-assembly method, wherein the polycation electrolyte was polycation electrolyte PEI containing NH2-ZIF-8(70), and the polyanion electrolyte was polyacrylic acid (PAA):

[0129] (1) A 4 g / L PAA solution (solute is PAA, solvent is 0.5 mol sodium chloride dissolved in 1 L deionized water to obtain a 0.5 M NaCl aqueous solution, and pH=7.3 is adjusted using a 1 M sodium hydroxide aqueous solution) with a polyelectrolyte solution having a temperature of 22°C is injected into the lumen of a polyethersulfone hollow fiber ultrafiltration membrane through a peristaltic pump and allowed to stand for 5 min to form a first layer of coating; the lumen of the membrane is flushed with deionized water for 4 min until the conductivity of the eluate is close to that of deionized water, and then the excess liquid in the lumen of the membrane is blown dry with compressed air;

[0130] (2) injecting 10 g / L of polycation electrolyte PEI solution containing NH2-ZIF-8(70) (the solute is polycation electrolyte PEI containing NH2-ZIF-8(70), the solvent is 2.5 M NaCl aqueous solution obtained by dissolving 2.5 mol sodium chloride in 1 L deionized water, and the pH is adjusted to 3.5 using 1 M hydrochloric acid aqueous solution), the temperature of the polyelectrolyte solution is 22 °C, and it is injected into the inner cavity of the hollow fiber membrane coated with PSS through a peristaltic pump, and allowed to stand for 5 minutes to form a second layer of coating; flushing the inner cavity of the membrane with deionized water for 4 minutes until the conductivity of the eluate is close to the conductivity of deionized water, and then blowing the excess liquid in the membrane cavity with compressed air;

[0131] (3) The above steps (1) and (2) are repeated alternately until eight monolayers are formed to obtain a polyelectrolyte composite nanofiltration membrane containing NH2-ZIF-8(70).

[0132] By increasing the molar percentage of NH2-ZIF-8(70) in the amino-containing polycationic electrolyte from 30% to 70%, the retention rates of the nanofiltration membrane for MgSO4, MgCl2, NaCl, and Na2SO4 were 98%, 99%, 55%, and 19%, respectively.

[0133] Example 6

[0134] The preparation method of the composite hollow fiber nanofiltration membrane in this embodiment comprises the following steps:

[0135] NH2-ZIF-8 (70) was prepared according to the method and conditions of Example 5;

[0136] 1.4 mol NH2-ZIF-8(70) and 0.6 mol polyethyleneimine (PEI) were mixed to obtain a polycationic electrolyte PEI containing NH2-ZIF-8(70), wherein the molar percentage of NH2-ZIF-8(70) was 70%;

[0137] The polyethersulfone hollow fiber ultrafiltration membrane was coated with polyelectrolyte solutions with opposite charges alternately by layer-by-layer self-assembly method, wherein the polycation electrolyte was polycation electrolyte PEI containing NH2-ZIF-8(70), and the polyanion electrolyte was polyacrylic acid (PAA):

[0138] (1) A 10 g / L solution of a polycation electrolyte PEI containing NH2-ZIF-8(70) (the solute is a polycation electrolyte PEI containing NH2-ZIF-8(70), the solvent is a 2.5 M NaCl aqueous solution obtained by dissolving 2.5 mol sodium chloride in 1 L deionized water, and the pH is adjusted to 3.5 using a 1 M hydrochloric acid aqueous solution), the temperature of the polyelectrolyte solution being 22° C. is injected into the lumen of a polyethersulfone hollow fiber membrane through a peristaltic pump and allowed to stand for 5 min to form a first coating layer; the lumen of the membrane is flushed with deionized water for 4 min until the conductivity of the eluate is close to that of deionized water, and then the excess liquid in the lumen of the membrane is blown dry with compressed air;

[0139] (2) Inject 4 g / L PAA solution (solute is PAA, solvent is 0.5 mol sodium chloride dissolved in 1 L deionized water to obtain 0.5 M NaCl aqueous solution, and use 1 M sodium hydroxide aqueous solution to adjust pH = 7.3), the temperature of the polyelectrolyte solution is 22 ° C, and inject it into the lumen of the hollow fiber membrane coated with PEI through a peristaltic pump, and let it stand for 5 minutes to form a second layer of coating; flush the membrane lumen with deionized water for 4 minutes until the conductivity of the eluate is close to the conductivity of deionized water, and then use compressed air to blow dry the excess liquid in the membrane lumen;

[0140] (3) The above steps (1) and (2) are repeated alternately until eight monolayers are formed to obtain a polyelectrolyte composite nanofiltration membrane containing NH2-ZIF-8(70).

[0141] The first layer of the coating polyelectrolyte is set as a polycation electrolyte, and the retention rates of the nanofiltration membrane for MgSO4, MgCl2, NaCl, and Na2SO4 are 97%, 99%, 47%, and 15%, respectively.

[0142] It can be seen from the above embodiments that the present invention prepares amino-functionalized NH2-ZIF-8 by in-situ substitution of 2-methylimidazole in the metal organic framework ZIF-8 structure with 2-aminoimidazole; the above-mentioned NH2-ZIF-8 containing an amino structure and a polycation electrolyte are prepared on a base membrane by a layer-by-layer self-assembly method to prepare a hollow fiber composite nanofiltration membrane. The prepared nanofiltration membrane can not only improve the retention rate of divalent cations, but also has a higher pure water flux, which is beneficial for application in sewage purification, seawater desalination and biomaterials.

[0143] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a composite hollow fiber nanofiltration membrane, characterized in that: The following steps are involved: Mixing 2-methylimidazole, 2-aminoimidazole and a first organic solvent to obtain an imidazole solution; dispersing the zinc salt in a second organic solvent to obtain a zinc salt dispersion; The imidazole solution is mixed with the zinc salt dispersion to carry out coordination reaction to obtain NH2-ZIF-8 material; The NH2-ZIF-8 material is mixed with a polycation electrolyte to obtain an amino-structured polycation electrolyte; The composite hollow fiber nanofiltration membrane is obtained by using a layer-by-layer self-assembly method and using polyelectrolyte solutions with opposite charges to perform alternate coating treatment on the hollow fiber ultrafiltration membrane. The polyelectrolyte in the polyelectrolyte solution with opposite charges is the polycation electrolyte or polyanion electrolyte containing an amino structure.

2. The preparation method according to claim 1, characterized in that: The molar amount of the 2-aminoimidazole is 10 to 100% of the total molar amount of the 2-methylimidazole and the 2-aminoimidazole.

3. The preparation method according to claim 1, characterized in that: The molar ratio of zinc ions to the total molar amount of 2-methylimidazole and 2-aminoimidazole in the zinc salt is 1:1 to 1:

60.

4. The preparation method according to any one of claims 1 to 3, characterized in that The coordination reaction time is 30 to 60 minutes.

5. The preparation method according to claim 1, characterized in that: The molar amount of the NH2-ZIF-8 material is 1-70% of the molar amount of the amino-containing polycationic electrolyte; the mixing time of the NH2-ZIF-8 material and the polycationic electrolyte is 30-60 minutes, and the temperature is 15-25°C.

6. The preparation method according to claim 1, characterized in that: The polycation electrolyte comprises one of polydimethyldiallylammonium chloride, polyethyleneimine, polyethyleneamine and polyacrylamide; The polyanion electrolyte includes one of polyacrylic acid, polyaminoacetic acid and polystyrene sulfonic acid.

7. The preparation method according to claim 1 or 6, characterized in that: The total number of polyelectrolyte coating layers formed by the alternating coating process is 5 to 20 layers; The temperature of the alternating coating treatment is independently 15-25°C.

8. The preparation method according to claim 7, characterized in that: When the polyelectrolyte coating is a polycationic coating, the pH of the polyelectrolyte solution used is 3.5-4.5; when the polyelectrolyte coating is a polyanionic coating, the pH of the polyelectrolyte solution used is 6.0-8.

0.

9. The composite hollow fiber nanofiltration membrane prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the composite hollow fiber nanofiltration membrane according to claim 9 in the fields of surface water treatment, biopharmaceuticals, seawater desalination or soil and groundwater remediation.

Citation Information

Patent Citations

  • High-flux high-interception-rate positive charge composite nanofiltration membrane and preparing method of high-flux high-interception-rate positive charge composite nanofiltration membrane

    CN105013333A

  • Positively charged composite nano filtration membrane and preparation method

    CN109794166A

  • Preparation method for back-diffusion in-situ self-assembled MOFs nanofiltration membrane

    CN105126638A

  • Metal organic framework ZIF-8 membrane, preparation method and application thereof

    CN112717706A